2008
DOI: 10.1111/j.1524-4725.2008.34339.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress of Immunostains in Mohs Micrographic 
Surgery: A Review

Abstract: Mohs micrographic surgery is often considered the treatment of choice for a variety of skin malignancies. In recent years, the application of immunostaining techniques has facilitated the successful removal of a number of common and less common cutaneous malignancies, including basal cell carcinoma, squamous cell carcinoma, malignant melanoma, dermatofibrosarcoma protuberans, microcystic adnexal carcinoma, sebaceous carcinoma, atypical fibroxanthoma, extramammary Paget's disease, and even sarcomas. Immunostain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 120 publications
0
13
0
2
Order By: Relevance
“…There has been a recent review 8 on the current uses of immunostaining in MMS and the authors concluded that immunohistochemical technique has played an important role in MMS advancement. 8 This article compares all patients treated with MMS at SCFA, Westmead in 1997 against those treated in 2007 at the same institution with the objective of evaluating changes in the type of patients, type of skin cancer, and repair used to close the defects after surgery.…”
mentioning
confidence: 99%
“…There has been a recent review 8 on the current uses of immunostaining in MMS and the authors concluded that immunohistochemical technique has played an important role in MMS advancement. 8 This article compares all patients treated with MMS at SCFA, Westmead in 1997 against those treated in 2007 at the same institution with the objective of evaluating changes in the type of patients, type of skin cancer, and repair used to close the defects after surgery.…”
mentioning
confidence: 99%
“…In MAC, staining is scattered and peripheral, particularly in deeper parts of the tumor. Epithelial membrane antigen is positive in MAC and helps differentiate from morphoeic BCC [ 40 ] . Staining for cytokeratin 15 may be useful in excluding basal-cell and squamous cell carcinoma but not desmoplastic trichoepithelioma [ 41 ] .…”
Section: Histopathological Featuresmentioning
confidence: 99%
“…Some special stains are especially useful in banal-appearing tumors, specifically if significant inflammation is present to mask the tumor cells. Special stains include CEA, AE1/AE3, and EMA which all stain positive and others like CK20 which stains negative (Thosani et al, 2008).…”
Section: Histological Features Of Macmentioning
confidence: 99%